Polarization over Energy and Climate in Canada: Canada's Climate Performance, Renewables, Nuclear, Community Roles - Aguirre, Rafael; Frank, Brendan; Gattinger, Monica (Université d'Ottawa | University of Ottawa, 2021)
This third report on polarization is based on the large survey (n=2600) carried out in 2019. It examines views about the development of nuclear and renewable energy in Canada, and the role of communities, Indigenous Peoples, and the federal and provincial governments.
Keywords: Climate Change; Polarization; Public Opinion; Surveys; Renewable energy; energy policy; Canada; nuclear energy